Women and Nation-Building - Benard, Cheryl (RAND Corporation, 2008)
Using a case study of Afghanistan, this study examines gender-specific impacts of conflict and post-conflict and the ways they may affect women differently than they affect men. It analyzes the role of women in the nation-building process and considers outcomes that might occur if current practices were modified. Recommendations are made for improving data collection in conflict zones and for enhancing the outcomes of nation-building programs.